Role of Al-Qur'an Read and Write Ability toward Achievement of Islamic Education for Students at SDN Inpres 12/79 Kampuno Attobaja Village Barebbo Sub-District Bone Regency - Harta, Muhammad (Journal of Islam and Science, 2020)
This study examines the ability to read and write Al Qur’an and its effect on learning achievement of Islamic education for students at SDN Inpres 12/79 Kampuno, Barebbo Sub-district, Bone Regency with main issues (1) What is the level of reading and writing ability of the Qur’an for students in SDN Inpres 12/79 Kampuno, Barebbo Sub-district, Bone Regency? (2) What factors influence the ability to read and write the Qur'an for students at SDN Inpres 12/79 Kampuno, Barebbo Sub-district, Bone Regency? (3) the effect of reading and writing al-Qur'an on the learning achievement of Islamic education at SDN Inpres 12/79 Kampuno, Barebbo Sub-district, Bone Regency?. To answer these problems, the authors use library research, that is, researchers examine theories in books relating to reading and writing of the Qur’an and field research, researchers examining data taken in the field, which consists of questionnaires, interviews (interviews), observations, documentation and data analysis methods inductively, deductively and comparatively. Results showed that the ability to read and write Al Qur’an for students in SDN Inpres 12/79 Kampuno, Barebbo Sub-district, Bone Regency was fluent. Factors that influence the learning achievement of Islamic education for students in SDN Inpres 12/79 Kampuno, Barebbo Sub-district, Bone Regency are internal and extrenal factors. The ability to read and write the Qur'an has a significant influence on the learning achievement of Islamic education for students in SDN Inpres 12/79 Kampuno, Barebbo Sub-district, Bone Regency.